2018
DOI: 10.3390/ijgi7010008
|View full text |Cite
|
Sign up to set email alerts
|

Cartographic Redundancy in Reducing Change Blindness in Detecting Extreme Values in Spatio-Temporal Maps

Abstract: Abstract:The article investigates the possibility of using cartographic redundancy to reduce the change blindness effect on spatio-temporal maps. Unlike in the case of previous research, the authors take a look at various methods of cartographic presentation and modify the visual variables in order to see how those modifications affect the user's perception of changes on spatio-temporal maps. The study described in the following article was the first attempt at minimizing the change blindness phenomenon by man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
(80 reference statements)
3
4
0
1
Order By: Relevance
“…They concluded that vividness/distinctiveness is a major factor of route memorization. This corresponds to Cybulski and Medyńska-Gulij's [39] findings that cartographic redundancy is influential in the change detection of animated stimuli.…”
Section: Related Researchsupporting
confidence: 83%
See 1 more Smart Citation
“…They concluded that vividness/distinctiveness is a major factor of route memorization. This corresponds to Cybulski and Medyńska-Gulij's [39] findings that cartographic redundancy is influential in the change detection of animated stimuli.…”
Section: Related Researchsupporting
confidence: 83%
“…Already, Wilkening and Fabrikant [69] noticed in their research that time pressure negatively affects map-based related tasks. The difficulty is an aspect of the animation that is crucial for effectiveness, as has been proven in many recent studies [8,25,39]. Moreover, this study proves that the number of turns of an animated route reduces the effectiveness of memorizing by several percent.…”
Section: Discussionsupporting
confidence: 69%
“…Cartographers explored a number of ways to reduce cognitive load and make animations more accessible. While many ideas are related to the user interface design with the implicit or explicit goal to minimize split attention and/or maximize user control [9][10][11][12][13][14], others focus on the transition between time-steps [15,16], on techniques to highlight important changes [17], or on the relation between data complexity and animation speed. Multimäki and Ahonen-Rainio [18] equalize the temporal scale according to the temporal density of change, slowing down the animation in busy times, while increasing animation pace when the number of changes is low.…”
Section: Solutions Proposed To Reduce Cognitive Loadmentioning
confidence: 99%
“…W kontekście map animowanych analogiczne badania przeprowadzili P. Cybulski i B. Medyńska-Gulij (2018). Autorzy użyli zmiennych grafi cznych wielkości oraz barwy do zakodowania danych o odniesieniu punktowym (wielkość opadów atmosferycznych, ryc.…”
Section: Defi Nicja I Poglądy Na Redundancjęunclassified